Epigenetic Modifications of Histones in Periodontal Disease. (February 2016) - Martins, M.D.; Jiao, Y.; Larsson, L.; Almeida, L.O.; Garaicoa-Pazmino, C.; Le, J.M.; Squarize, C.H.; Inohara, N.; Giannobile, W.V.; Castilho, R.M.
Periodontitis is a chronic infectious disease driven by dysbiosis, an imbalance between commensal bacteria and the host organism. Periodontitis is a leading cause of tooth loss in adults and occurs in about 50% of the US population. In addition to the clinical challenges associated with treating periodontitis, the progression and chronic nature of this disease seriously affect human health. Emerging evidence suggests that periodontitis is associated with mechanisms beyond bacteria-induced protein and tissue degradation. Here, we hypothesize that bacteria are able to induce epigenetic modifications in oral epithelial cells mediated by histone modifications. In this study, we found that dysbiosis in vivo led to epigenetic modifications, including acetylation of histones and downregulation of DNA methyltransferase 1. In addition, in vitro exposure of oral epithelial cells to lipopolysaccharides resulted in histone modifications, activation of transcriptional coactivators, such as p300/CBP, and accumulation of nuclear factor–κB (NF-κB). Given that oral epithelial cells are the first line of defense for the periodontium against bacteria, we also evaluated whether activation of pathogen recognition receptors induced histone modifications. We found that activation of the Toll-like receptors 1, 2, and 4 and the nucleotide-binding oligomerization domain protein 1 induced histone acetylation in oral epithelial cells. Our findings corroborate the emerging concept that epigenetic modifications play a role in the development of periodontitis.